Analysis of English Alive Textbook in Terms of Genres and Lexical Density - Leffi Noviyenti (STAI Hubbulwathan Duri, 2021)
The current study aimed at analyzing an English textbook titled English Alive used by English teachers from some senior high schools in Curup, Bengkulu, Indonesia. The textbook analysis was oriented towards two domains, namely genres and lexical density, by applying a content analysis method. This study revealed that the English Alive textbook had five genres: reading materials in the narrative, report, analytical exposition, spoof, and hortatory exposition. Those genres were embedded in sixteen passages distributed to the entire textbook, and those passages were mapped into ten units. Lexical density measurement indicated that most of the passages were categorized as easy to be comprehended, and a few passages were categorized as too easy to be comprehended. However, text genres in this textbook did not sufficiently conform to the distribution of English reading materials as suggested by the K-13 curriculum. Some reading passages did not seem contributive to students’ English acquisition according to comprehensible input theory and other related findings. Hence, the English Alive textbook could be used in today’s context and needs as supplementary material, but the primary reading materials should be resting upon K-13-driven English textbooks. Strength and weaknesses were also identified from the English Alive textbook. The former could be noted that this textbook adopted the constructivism theory and genre-based approach properly. However, the latter indicated that the provision of genre materials did not entirely conform to essential competencies formulated in the current K-13 curriculum of English education. Further studies could analyze more textbooks to help teachers choose appropriate English textbooks.